The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jof7080614
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the Quality and Storage Life of Button Mushrooms (Agaricus bisporus) with Gum, Agar, Sodium Alginate, Egg White Protein, and Lecithin Coating

Abstract: Button mushrooms have a very short shelf life after harvesting and are sensitive to mechanical damage and browning. This can be a severe problem in enlarging the market and the long-distance exportation of this product. In this respect, edible coatings could be an alternative treatment to extend the shelf life of button mushrooms, maintaining their quality during long-term storage. The aim of this study was to investigate the impact of gum, agar, sodium alginate, egg white protein, and lecithin on the postharv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The lowest weight loss (%) was observed in the sample coated with aloe vera and gelatin during its 16 days of shelf life. Our results are in accordance with the study of Cavusoglu et al (2021), who evaluated the effects of different coatings on the weight loss (%) of button mushrooms. They reported that sodium alginate was better than other coatings for reducing the weight loss (%) of samples.…”
Section: Weight Losssupporting
confidence: 92%
See 1 more Smart Citation
“…The lowest weight loss (%) was observed in the sample coated with aloe vera and gelatin during its 16 days of shelf life. Our results are in accordance with the study of Cavusoglu et al (2021), who evaluated the effects of different coatings on the weight loss (%) of button mushrooms. They reported that sodium alginate was better than other coatings for reducing the weight loss (%) of samples.…”
Section: Weight Losssupporting
confidence: 92%
“…There are no differences in a* value of all samples. Also, the protective effect of edible coatings such as gum, agar, sodium alginate, egg white protein, and (Cavusoglu et al, 2021), chitosan (Sami et al, 2021), pectin, chitosan, sodium alginate, and CMC (Pleșoianu and Nour, 2022) against color changes were reported previously. Our results demonstrated that the applied coating may be a potential approach to maintaining the freshness and extending the shelf life of the button mushroom during storage.…”
Section: Color Propertiesmentioning
confidence: 71%
“…Mushroom color is one of the most important indicators in consumer preference. An L* value lower than 80 reduces the marketability of mushrooms [ 32 , 33 ] and a value less than 69 is considered unmarketable for product [ 34 ]. In the current study, AL and FA inoculations led to relatively little change in L* values during the storage period.…”
Section: Resultsmentioning
confidence: 99%
“…FA application resulted in negative effects with respect to browning index and yellowness index values in white button mushrooms. There are some edible coatings to inhibit color changes during the storage period [ 32 ], but this type of treatment will need additional labor and result in an increase in expenses. In this respect, PGPR applications during the production stage can offer a solution to inhibit significant color changes during the marketing or storage period of white button mushrooms.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have explained the relationships between biochemical and physicochemical parameters (ethylene production and respiratory rate, etc.) using principal component (PCA) and bivariate analyses [18][19][20]. However, more detailed research is needed to reveal the relationships between those variables and explain complex interrelationships.…”
Section: Introductionmentioning
confidence: 99%